Standardization and Alignment of Student Learning Outcomes for Sociology Courses in Maryland Public Colleges - Randall Salm; Emma Bate; Annie Ruth Leslie (Teaching and Learning Excellence through Scholarship)
In Spring 2020, the Chancellor of the University System of Maryland (USM) and the President of the Maryland Association of Community Colleges (MACC) asked the provosts of MACC and USM institutions to address the course transfer process between the 2-year and 4-year schools and created the MD Provosts Transfer Council (PTC) which was made up of Provosts or Vice Presidents from several MD public colleges. The leadership requested a course outcomes-based transfer process that would allow students to seamlessly transfer credits and courses from their home institutions to receiving transfer institutions. The process started with the development of affinity groups for the top MD academic transfer programs and the highest-enrolled general education courses, which included sociology. The MD Sociology Affinity Group started in Fall 2020.